72 Medical leadership and management teaching to medical students; evaluation of a student-selected component. (16th November 2020) - Muneeb, Ferhan; Pandya, Tej; Gibb, Jonathan; Metcalfe, Neil
Abstract : Aims: Identify effective methods of teaching medical leadership and management (MLM) content to undergraduate medical students Gauge student opinions on the importance of MLM content in the training of doctors and whether its current level of provision on the curriculum is sufficient. Background: Historically, a significant proportion of healthcare leaders in the National Health Service have come from non-medical backgrounds despite the evidence base showing that outcomes for both patients and organisations improve when clinicians assume positions of senior authority. However, as MLM education provision remains in its infancy, no decisive evidence-based strategy has materialised to inform the development of this curriculum. Methods: This project targeted penultimate and final year medical students at the University of Manchester (n=40), aiming to develop MLM skills through a four-week student selected component (SSC). This included small group, expert led tutorials as well as opportunities to attend coroners' courts and fitness to practice tribunals. Satisfactory completion of the module required the production of a quality improvement project or lay document for the public. Students opinions and confidence in MLM concepts were evaluated with a survey utilising a 5-point Likert scale pre and post placement. Results: Our results demonstrated a significant increase in student's confidence of their knowledge in medical authorities and NHS structures compared to before this placement. Furthermore, the vast majority of students believed that greater emphasis should be made on MLM content within the core curriculum. Conclusions: There is an appetite for further MLM education provision on the undergraduate medical curriculum with the methods employed on this SSC being an effective way of teaching this content. Further research should aim at expanding this to larger cohorts and investigating how this content can be longitudinally applied over the length of the course.